2001
DOI: 10.3748/wjg.v7.i4.500
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor and its role in oncogenesis of human gastric carcinoma

Abstract: This study provides direct evidence that VEGF plays an important role in the oncogenesis of human gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 58 publications
1
15
0
2
Order By: Relevance
“…VEGF is the major angiogenic cytokine mediator; therefore, it is crucial for tumor development and metastasis [8]. In addition to macrophages and cancer infiltrating T cells [19], VEGF is expressed by several human solid tumors including PCa [20][21][22][23][24][25][26][27]. VEGF over-expression in prostate tumors has been correlated with increased tumor microvessel density [28], disease progression, lymph node metastasis, resistance to treatment, and poor survival [10].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is the major angiogenic cytokine mediator; therefore, it is crucial for tumor development and metastasis [8]. In addition to macrophages and cancer infiltrating T cells [19], VEGF is expressed by several human solid tumors including PCa [20][21][22][23][24][25][26][27]. VEGF over-expression in prostate tumors has been correlated with increased tumor microvessel density [28], disease progression, lymph node metastasis, resistance to treatment, and poor survival [10].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, vascular endothelial growth factor (VEGF) is considered to be one of the strongest promoters of angiogenesis in gastrointestinal tumors 5, which stimulates proliferation, migration of tumor cell and regulates vascular permeability 6. Over‐expression of VEGF has been correlated with angiogenesis and prognosis in different tumors, including breast 7, lung 8 as well as gastric cancer (GC) 9–12.…”
Section: Introductionmentioning
confidence: 99%
“…Various molecules belonging to the vascular endothelial growth factor (VEGF) family are thought to regulate the lymphatic vessel development [12,13]. Some studies have demonstrated that VEGF factor C (VEGF-C) expression is closely associated with the prognosis of breast [14], lung [15], stomach [16], and colorectal [17] cancers. VEGF mediates angiogenesis and vascular permeability [18].…”
Section: Introductionmentioning
confidence: 99%